Carbon isotope composition as a tool to control the quality of herbs and medicinal plants - Marchese, J. A.; Ming, L. C. [UNESP]; Ducatti, C. [UNESP]; Broetto, F. [UNESP]; Da Silva, E. T. [UNESP]; Leonardo, M. [UNESP] (Institute of Experimental Botany, 2006)
Isotope screening is a simple test for determining the photosynthetic pathway used by plants. The scope of this work was to classify the photosynthetic type of some herbs and medicinal plants through studies of the carbon isotope composition (δ13C). Also, we propose the use of carbon isotope composition as a tool to control the quality of herbs and medicinal plants. For studies of δ13C, δ 13C‰ = [R (sample)/R (standard) - 1] × 10-3, dry leaves powdered in cryogenic mill were analyzed in a mass spectrometer coupled with an elemental analyzer for determining the ratio R = 13CO2/12CO2. In investigation of δ13C of 55 species, 23 botanical families, and 44 species possessed a C3 photosynthetic type. Six species found among the botanical families Euphorbiaceae and Poaceae were C4 plants, and 5 species found among the botanical families Agavaceae, Euphorbiaceae, and Liliaceae possessed CAM-type photosynthesis. Carbon isotope composition of plants can be used as quality control of herbs and medicinal plants, allowing the identification of frauds or contaminations. Also, the information about the photosynthetic type found for these plants can help in introducing and cultivating exotic and wild herbs and medicinal plants.
Keywords: C3, C4, and CAM plants; Photosynthetic mechanisms; Agavaceae; Crassulaceae; Euphorbia; Euphorbiaceae; Liliaceae; Magnoliophyta; Poaceae